Gender Roles In Islamic Primary Schools In South Sulawesi - Siti Azisah (Universitas Islam Negeri Alauddin Makassar, 2013)
This paper investigated gender roles in three Islamic Primary schools in South Sulawesi including one state Islamic primary school in Bone Regency, one private Islamic primary school in Wajo Regency and one private Islamic primary school in Makassar city. These three schools represents three different socio-culture economic backgrounds in South Sulawesi. The data were gathered using qualitative interviews and observations. The schools principals, teachers and the head of school commitee were interviews in-deptly and their activities concerning gender roles were observed including in school meeting and teaching-learning process. Then, the data were analysed qualitatively. This study uncovered three main points: 1) The three school communities shared stereotyped gender role ideology and practices; 2) They have low level of knowledge and opinion about gender mainstreaming; and 3) they have different gender practices. These genders roles of the school community influence the teaching of character education to their students.